1994
DOI: 10.1063/1.112804
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic vapor phase epitaxial growth of AlP/GaP monolayer superlattice using tertiarybutylphosphine

Abstract: The growth interruption time in the organometallic vapor phase epitaxial growth of AlP/GaP layers using tertiarybutylphosphine is optimized for the realization of an AlP/GaP monolayer superlattice. In the growth interruption, there exists an optimum time (2 s) beyond which the full width at half-maximum (FWHM) of the x-ray diffraction satellite peaks of an (AlP)5/GaP)5 superlattice becomes broader. The monolayer (AlP)1/(GaP)1 superlattice is realized for the first time in a AlP/GaP system. An average heteroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Thus a great deal of experimental work has been devoted to these materials. The unusual optical behaviour of AlP/GaP SLs has been extensively studied using photoluminescence, magneto-photoluminescence, 9,10,11 optical absorption, 12 X-ray diffraction 13 and refractive index measurements. 14 InP/GaP, being one of the material combinations which spontaneously constructs the SL under specific conditions, has been subject to numerous experimental works 15,16,17 including cathodoluminescence experiments 18,19,20 and studies on the influence of pressure, SL period and barrier thickness 21,22,23 on the optical transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus a great deal of experimental work has been devoted to these materials. The unusual optical behaviour of AlP/GaP SLs has been extensively studied using photoluminescence, magneto-photoluminescence, 9,10,11 optical absorption, 12 X-ray diffraction 13 and refractive index measurements. 14 InP/GaP, being one of the material combinations which spontaneously constructs the SL under specific conditions, has been subject to numerous experimental works 15,16,17 including cathodoluminescence experiments 18,19,20 and studies on the influence of pressure, SL period and barrier thickness 21,22,23 on the optical transitions.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction 13 and refractive index measurements. 14 InP/GaP, being one of the material combinations which spontaneously constructs the SL under specific conditions, has been subject to numerous experimental works 15,16,17 including cathodoluminescence experiments 18,19,20 and studies on the influence of pressure, SL period and barrier thickness 21,22,23 on the optical transitions.…”
mentioning
confidence: 99%
“…They found that the superlattice is a direct band-gap material when m and n, the number of monolayers in GaP and AlP respectively, are both odd and greater than three monolayers. Furthermore, it was observed from PL and electrore ectance (ER) measurements that the superlattice has a Type-II band line-up at the interface [3][4][5]. The origin of enhanced photoluminescence from short-period GaP/AlP SLs was investigated by Nakayama and co-workers [6,7].…”
Section: Introductionmentioning
confidence: 97%